Electrode for energy storage device and method for producing dry electrode film for energy storage device

Hyperfibrillated binder and carbon particles in a dry process produce thinner, stronger electrode films for lithium ion capacitors, addressing thickness and resistance issues in conventional films, enhancing power density and manufacturing efficiency.

JP7610633B2Active Publication Date: 2025-01-08テスラインコーポレーテッド
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023018078
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2016-03-01
Filing Date
2023-02-09
Publication Date
2025-01-08
Estimated Expiration
2037-02-27

AI Technical Summary

Technical Problem

Conventional dry electrode films for energy storage devices, such as lithium ion capacitors, are thick and difficult to compress, leading to increased volume and equivalent series resistance, which affects electrical performance and manufacturing efficiency.

Method used

The use of hyperfibrillated binder particles and carbon particles in a dry manufacturing process to create a free-standing electrode film with reduced binder content, enhanced fibrillation, and controlled calendering to achieve thinner films with improved mechanical strength and reduced equivalent series resistance.

Benefits of technology

The method results in thinner electrode films with enhanced mechanical properties and reduced equivalent series resistance, leading to improved power density and manufacturing efficiency of lithium ion capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610633000001
    Figure 0007610633000001
  • Figure 0007610633000002
    Figure 0007610633000002
  • Figure 0007610633000003
    Figure 0007610633000003
Patent Text Reader

Abstract

A cheaper and / or faster method for producing thinned electrode films and compositions for electrodes for energy storage devices is provided. The energy storage device (100) includes a cathode (102), an anode (104), a separator (106), and an electrolyte (122) disposed within a housing (120). The anode and / or electrode includes an electrode film (112-118) containing an ultrafibrillated binder material and carbon. The electrode film has a reduced binder content while maintaining desirable mechanical and / or electrical performance. The method for manufacturing an electrode film includes a fibrillation process using a slower speed and / or a higher processing pressure to enhance the fibrillation of the binder material. The electrode film contains a conductivity-promoting additive to promote a reduction in equivalent series resistance. Enhanced fibrillation of the binder material facilitates the formation of thinner electrode films, such as dry electrode films.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to energy storage devices, and more particularly to compositions and methods of making electrodes for energy storage devices. [Background technology]

[0002] Various types of energy storage devices can be used to power electrical devices. Such electrical devices include, for example, capacitors, batteries, capacitor-battery hybrids, and / or fuel cells. Energy storage devices such as lithium ion capacitors can improve the composition of their electrodes to improve the electrical performance of the capacitor. Summary of the Invention

[0003] For purposes of summarizing the invention and the advantages achieved by the invention over the prior art, certain objects and advantages are described herein. Not necessarily all such objects or advantages will be achieved in accordance with any particular embodiment. Thus, for example, one skilled in the art will recognize that the invention can be embodied or practiced in a manner that achieves or optimizes one or a group of advantages described herein, without necessarily achieving other objects or advantages described or suggested herein.

[0004] In a first embodiment, a dry carbon particle, a dry superfibrillated binder particle, and a current collector are provided. An electrode for use in an energy storage device is provided comprising a free-standing dry electrode film and a body.

[0005] In one embodiment of the first aspect, the dry electrode film has a thickness of about 50 μm to about 120 μm. In one embodiment of the first aspect, the electrode is an anode. In one embodiment of the first aspect, the free-standing dry electrode film further contains conductive carbon. In one embodiment of the first aspect, the electrode film contains about 1% by weight to about 5% by weight of conductive carbon. In one embodiment of the first aspect, the electrode contains an electrolyte containing a lithium salt. In one embodiment of the first aspect, the electrolyte is further in ionic contact with the cathode. In one embodiment of the first aspect, the dried ultrafibrillated biomass is in ionic contact with the The ethylenediamine particles constitute about 3% to about 7% by weight of the free-standing dry electrode film. In one embodiment of the present invention, a lithium ion capacitor is provided that includes an electrode.

[0006] In a second embodiment, dried carbon particles and dried fibrillizable binder particles are forming a first dry electrode mix containing a biphenyl and a biphenyl in the dry electrode mix; The method includes ultrafibrillating the ductile matrix to form a superfibrillated matrix in the electrode film mixture, and calendering the superfibrillated electrode film mixture to form a free-standing superfibrillated electrode film.

[0007] In one embodiment of the second aspect, the method is substantially free of processing additives. In one embodiment of the second aspect, the method includes the step of forming a free-standing electrode film. In one embodiment of the second aspect, the method further includes contacting the first electrode with a current collector to form a first electrode. In one embodiment of the second aspect, the first electrode is an anode. In one embodiment of the second aspect, the free-standing dry electrode film has a thickness of about 50 μm to about 120 μm. In one embodiment of the second aspect, the dry ultrafibrillated binder is The particles contain about 3% to about 7% by weight of the superfibrillated matrix. In one embodiment of the second aspect, the step of forming the first mixture further includes a step of adding conductive carbon particles to the first mixture. In one embodiment of the second aspect, the first mixture contains about 1% by mass to about 5% by mass of the conductive carbon particles. In the present invention, the step of ultrafibrillating the binder includes the steps of fibrillating the binder in the dry electrode film mixture to form a first fibrillated matrix, breaking the first fibrillated matrix to form a powder mixture of carbon particles and fibrillated binder particles, and fibrillating the powder mixture to form a second fibrillated matrix comprising the ultrafibrillated matrix. forming a fibrillated matrix.

[0008] The specification contains at least one color drawing, copies of which are included in the claims and are hereby incorporated by reference. and the necessary fees.

[0009]

[0023] The present disclosure and other features, aspects, and advantages will be described with reference to drawings of specific embodiments, which are intended to illustrate specific embodiments and are not intended to limit the invention. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a side cross-sectional view illustrating a schematic example of an energy storage device according to an embodiment. [Diagram 2] FIG. 2 is a flow diagram showing an example of steps in a method for producing an electrode film. [Diagram 3] 1 is a table showing the equivalent series resistance performance of each of lithium ion capacitor cells having anodes with different types of conductivity-promoting additives. [Figure 4] FIG. 1 is a flow diagram showing an example of a method for manufacturing a thin electrode film. [Figure 5A] FIG. 2 is a schematic diagram of a payout machine for a calender line of an electrode film. [Figure 5B]FIG. 5B is a detailed view of a portion of the dispenser shown in FIG. 5A. [Figure 6A] 1 shows an SEM image of an electrode film prepared by prior art dry electrode processing. [Figure 6B] FIG. 1 shows SEM images of electrode films prepared by dry electrode processing using an ultrafibrillating binder. [Figure 7] 1 is a table showing data for various embodiments of lithium ion capacitors having anodes made by the methods provided herein.

[0011] Although specific embodiments and examples are described below, those skilled in the art will recognize that the invention extends beyond the specifically disclosed embodiments and / or uses, obvious variations and equivalents thereof, and therefore the scope of the invention disclosed herein should not be limited by the specific embodiments described below.

[0012] In some embodiments, energy storage devices, such as lithium ion capacitors (LiCs), are provided that have improved electrical and / or mechanical performance. In some embodiments, the device can include electrodes that contain the improved electrode film composition, which can provide improved electrical and / or mechanical performance. In some embodiments, the electrodes can be anodes and / or cathodes.

[0013] Disclosed embodiments can include electrode film material blends, electrode films, electrodes, energy storage devices, and related methods that undergo enhanced fibrillation of the binder material compared to conventional methods, i.e., "superfibrillation" as defined and described herein. Many electrical and / or mechanical performance advantages can be realized through enhanced binder fibrillation.

[0014] For example, by enhancing the fibrillation of the binder, the adhesion of the binder and the strength of the film can be increased. Such an embodiment may enable the production of thinner films using the same or less amount of binder as a comparable film with a comparably non-fibrillated binder. The use of thinner films may be beneficial for dry electrode film technology, where the free-standing properties of the dry electrode film and other reasons traditionally result in thicker films than wet electrode processing methods. Furthermore, reducing the weight percentage of binder ("binder loading") in the electrode film relative to some of the other materials, such as conductive materials, has electrical performance advantages. For example, using a superfibrillated binder and reducing the amount of binder in the electrode film also reduces undesirable electrical series resistance (ESR) in devices using the film compared to conventional films with conventional fibrillated binders. It is possible.

[0015] In some embodiments, the anode and / or cathode electrode films can contain fibrillizable binder materials and other electrode materials, such as carbon. The electrode films can have low amounts of binder materials while maintaining desirable mechanical properties. Such desirable mechanical properties can be useful, for example, in the manufacture of energy storage devices. The mechanical properties required for one or more steps of the process may be related to the strength of the electrode film. For example, when producing electrodes by dry manufacturing methods, a freestanding electrode film may advantageously provide sufficient stability for rolling and other handling before the film is attached to a current collector. Additionally, enhanced fibrillation of the binder material may advantageously facilitate the formation of thinner electrode films that can withstand the tension of a calendar line. In some embodiments, electrode films containing an increased number of fibrils, greater fibril surface area, and / or longer fibrils may be reduced in thickness while still exhibiting sufficient mechanical strength to maintain the desired film integrity during film manufacture.

[0016] The method of manufacturing an electrode film can include a fibrillation process in which the processing speed is slowed and / or the processing pressure is increased to enhance fibrillation of the binder material, as compared to conventional electrode film fibrillation processes. For example, enhanced fibrillation can result in an increased number of fibrils, an increased fibril surface area, and / or longer fibrils from the binder material, allowing for the use of less binder material while maintaining desirable mechanical properties, as compared to conventional electrode film fibrillation processes. Such an increased number of fibrils, increased fibril surface area, and / or longer fibrils can allow for a more effective matrix structure to be established in the electrode film, which can provide one or more of the advantages set forth herein. It is believed that this more effective matrix structure, in some embodiments, results in increased tensile strength in the longitudinal direction, resistance to shear, compressive and / or torsional stresses, reduced film thickness, increased film density, and reduced binder content compared to conventional dry electrode technologies. In certain embodiments, the electrode films are free-standing electrode films with reduced binder content as demonstrated herein.

[0017] In certain embodiments, the electrode film is a free-standing electrode film containing ultrafibrillated binder particles and carbon particles. The ultrafibrillated binder particles are processed in the process 200 and and / or 400, and / or 401, which are binder particles produced according to the methods of production set forth herein. Ultrafibrillated binder particles are binder particles that are fibrillated, reduced in size, and then refibrillated; and include binder particles that are fibrillated at higher pressures, slower velocities, slower feed rates, and / or for longer periods of time than conventional fibrillation techniques. Superfibrillated binder particles can be structurally defined based on fibril number, fibril surface area, and / or fibril length, all of which are comparable to the fibrillation of conventional binders. The superfibrillated matrix referred to herein is the structure formed by the components of the electrode film mixture, which has been superfibrillated by the fibrillation process to a level where the binder particles are stuck together, but have not yet been compressed into an electrode film, as shown, for example, in FIG. 6B.

[0018] In some embodiments, the superfibrillated binder particles have a maximum dimension of less than about 3 μm (microns), less than about 2 μm, less than about 1 μm, less than about 0.5 μm, less than about 0.3 μm, less than about 0.1 μm, less than about 0.05 μm, less than about 0.03 μm, less than about 0.01 μm, or any value therebetween, e.g., The nanofibrillated matrix is ​​characterized by a nanometer size of about 0.01-3 μm, about 0.03-2 μm, about 0.05-1 μm, or about 0.1 μm-0.3 μm. In still other embodiments, the nanofibrillated matrix comprises carbon particles that contact at least 10%, at least 20%, at least 30%, at least 40%, at least 50%, at least 60%, at least 70%, at least 80%, at least 90%, at least 95%, or at least 99% of the surface area of ​​the nanofibrillated binder particles, or any range therebetween. In some embodiments, the nanofibrillated binder particles are present in at least twice the number in the electrode film as compared to a conventional dry processed electrode film of comparable binder mass.

[0019] Conventional dry electrode films made by dry processing from dry particle electrode film mixtures produced using standard techniques with conventional fibrillating binders are generally characterized by a thickness of about 120 μm or more for anodes and about 80 μm or more for cathodes. The reason for the difference in thickness between these two types of dry electrodes is that anode electrode films are more difficult to compress than cathode electrode films, for example, at least in part because the carbon material of the anode is more difficult to compress compared to the activated carbon of the cathode electrode film. Generally, such conventional cathode films have a thickness of about 80 μm to about 10,000 μm. The thickness of the anode film may range from about 120 μm to about 10,000 μm.

[0020] In some embodiments, enhanced fibrillation of the binder material over conventional dry electrode processes can facilitate the formation of thinner electrode films. Advantageously, thinner electrode films can occupy less volume and be used in lithium ion capacitors. In some embodiments, ultrafibrillation of the binder material can result in thinner electrode films of about 80 μm, 60 μm, or 50 μm or less while maintaining the structural integrity and / or electrical performance of otherwise similar conventional dry electrode films having conventional fibrillated dry binder materials. In some embodiments, the electrode film produced by one or more process steps described herein can have a thickness of about 120 μm, 80 μm, 60 μm, or even about 50 μm or less, where the electrode is optionally an anode. In some embodiments, enhanced fibrillation of the binder material can facilitate the formation of an anode electrode film having a thickness of less than 120 μm. In some embodiments, enhanced fibrillation of the binder material can facilitate the formation of a thin electrode film, e.g., less than 120 μm, less than 80 μm, less than 60 μm, less than 50 μm, less than 40 μm, less than 30 μm, etc. For example, the manufacture of thinner electrode films, such as anode electrode films having a thickness of less than 120 μm or less, and cathode electrode films having a thickness of less than 120 μm, less than 80 μm, or less. In some embodiments, thinner electrode films can provide lithium ion capacitors with improved power performance. In some embodiments, anodes used in lithium ion capacitors have a thickness of about 40 μm to about 50 μm. In some embodiments, the lithium ion catalyst comprises an electrode film having a thickness of about 120 μm, about 50 μm to about 120 μm, about 50 μm to about 80 μm, about 60 μm to about 100 μm, or about 80 μm to about 120 μm. The cathode used in the capacitor comprises an electrode film having a thickness of about 40 μm to about 80 μm, about 40 μm to about 70 μm, about 50 μm to about 80 μm, or about 50 μm to about 70 μm.

[0021] In some embodiments, the electrode film contains a conductivity-promoting additive to help reduce the equivalent series resistance. The additive may be carbon black and / or graphite. In some embodiments, the electrode film contains a reduced amount of binder material and a higher amount of one or more conductivity-promoting additives compared to conventional electrode films. As such, the electrode films according to embodiments exhibit reduced equivalent series resistance while maintaining desirable mechanical properties.

[0022] A lithium ion battery comprising one or more electrodes containing the electrode film composition described herein. Lithium ion capacitors advantageously exhibit reduced equivalent series resistance, thereby providing capacitors with greater power density compared to conventional electrode films. In some embodiments, the improved equivalent series resistance reduces heat generation, thereby reducing or avoiding heat dissipation in lithium ion capacitors with conventional electrode films. In some embodiments, lithium ion capacitors with one or more electrodes containing the electrode film compositions described herein exhibit more In some embodiments, one or more of the electrodes described herein may be used. Lithium ion capacitors containing the electrode compositions can have a variety of shapes, including prismatic, cylindrical, and / or button shapes. In some embodiments, lithium ion capacitors comprising the electrolytes described herein are used in hybrid electric vehicles (HEVs), prismatic, cylindrical, and / or button-shaped applications. It can be used to power plug-in hybrid electric vehicles (PHEVs), and / or electric vehicles (EVs).

[0023] Although the electrodes and energy storage devices described herein may be described in the context of lithium ion capacitors, embodiments may also include one or more batteries, with or without lithium. The electrode may be used in any of a number of energy storage devices and systems, such as batteries, capacitors, capacitor-battery hybrids, fuel cells, combinations thereof, and the like. In some embodiments, the electrode is a cathode or anode configured for use in an ultracapacitor, a lithium ion capacitor, or a lithium ion battery. In a preferred embodiment, the electrode is an anode configured for use in a lithium ion capacitor.

[0024] FIG. 1 is a schematic side cross-sectional view of an example of an energy storage device 100. The energy storage device 100 may be a lithium ion capacitor. Of course, it should be understood that other energy storage devices are within the scope of the present invention and may include batteries, capacitor-battery hybrids, and / or fuel cells. The energy storage device 100 may include a first electrode 102, a second electrode 104, and a separator 106 disposed between the first electrode 102 and the second electrode 104. For example, the first electrode 102 and the second electrode 104 may be disposed on opposite sides of the separator 106. The first electrode 102 may be a cathode and the second electrode 104 may be an anode, or vice versa (the first electrode 102 is an anode and the second electrode 104 is a cathode). The energy storage device 100 is The device 100 may include an electrolyte 122 that facilitates ionic transfer between the electrodes 102, 104 of the device 100. For example, the electrolyte 122 may be in contact with the first electrode 102, the second electrode 104, and the separator 106. The electrolyte 122, the first electrode 102, the second electrode 104, and the separator 106 may be contained within an energy storage device housing 120. For example, the energy storage device housing 120 may be configured to accommodate the first electrode 102, the second electrode 104, the separator 106, and the electrolyte 122 after the first electrode 102, the second electrode 104, the separator 106, and the electrolyte 122 are introduced and the energy storage device 100 is impregnated with the electrolyte 122. The energy storage device 122 may be sealed such that it is physically sealed from the environment outside the housing. Although the gas storage device 100 is shown as a dual electrode, dual layer device, other configurations, such as a single layer electrode, may be used. It will be appreciated that other types of

[0025] The energy storage device 100 can include any of a number of different types of electrolyte 122. For example, the device 100 can include the electrolyte of a lithium ion capacitor. The electrolyte can include a lithium source, such as a lithium salt, and a solvent, such as an organic solvent. In some embodiments, the lithium salt includes lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2), lithium trifluoromethanesulfonate (LiSO3CF3), combinations thereof, and / or the like. In some embodiments, the solvent of the lithium ion capacitor electrolyte can include one or more ethers and / or esters. For example, lithium The electrolyte solvent for the lithium ion capacitor is ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), vinyl carbonate (VCO), etc. For example, the electrolyte may include LiPF6, ethylene carbonate (VC), propylene carbonate (PC), combinations thereof, and / or the like. The carbonates may include propylene carbonate, and diethyl carbonate.

[0026] The separator 106 can be configured to electrically insulate two adjacent electrodes, e.g., the first electrode 102 and the second electrode 104, on opposite sides of the separator 106 while allowing ionic communication between the two adjacent electrodes. The separator 106 can be made of a variety of porous, electrically insulating, In some embodiments, the separator 106 comprises a polymeric material. For example, the separator 106 can be made of a cellulose material (e.g., paper), polyethylene, The material may include polyethylene (PE) materials, polypropylene (PP) materials, and / or polyethylene and polypropylene materials.

[0027] As shown in FIG. 1, the first electrode 102 and the second electrode 104 include a first current collector 108 and a second current collector 110, respectively. The first current collector 108 and the second current collector 110 can facilitate an electrical coupling between the corresponding electrode and an external circuit (not shown). The first current collector 108 and / or the second current collector 110 can be electrically connected to an external circuit (not shown). Current collector 110 may contain one or more conductive materials and / or may be coupled to a corresponding electrode and terminal for coupling energy storage device 100 to an external circuit, such as an external electrical circuit. The current collectors can be of various shapes and dimensions to facilitate transfer of charge between the electrodes. For example, the current collectors can include metallic materials such as materials including aluminum, nickel, copper, silver, and alloys thereof. For example, the first current collector 108 and / or the second current collector 110 can include aluminum foil of a rectangular or substantially rectangular shape and can be sized to provide a desired transfer of charge between the corresponding electrodes and an external electrical circuit (e.g., transfer of charge through the current collector plate and / or another component of the energy storage device configured to electrically couple the electrodes to an external electrical circuit).

[0028] The first electrode 102 comprises a first electrode film 112 (e.g., a top electrode film) on a first surface of the first current collector 108 (e.g., a top surface of the first current collector 108) and a second electrode film 114 (e.g., a bottom electrode film) on an opposing second surface of the first current collector 108 (e.g., a bottom surface of the first current collector 108). Similarly, the second electrode 104 comprises a first electrode film 116 (e.g., a top electrode film) on a first surface of the second current collector 110 (e.g., a top surface of the second current collector 110) and a second electrode film 114 (e.g., a bottom electrode film) on an opposing second surface of the first current collector 108 (e.g., a bottom surface of the first current collector 108). a second electrode film 118 on the opposing second surface (e.g., the bottom surface of the second current collector 110); For example, a first surface of the second current collector 110 faces the second surface of the first current collector 108, and the separator 106 is adjacent to the second electrode film 114 of the first electrode 102 and the first electrode film 116 of the second electrode 104.

[0029] The electrode films 112, 114, 116 and / or 118 can be of various suitable shapes, sizes and / or thicknesses. For example, the electrode films can have a thickness of about 30 μm to about 250 μm, including about 100 μm (microns) to about 250 μm.

[0030] In some embodiments, one or more of the electrode films, such as electrode films 112, 114, 116, and / or 118, can contain a mixture that contains a binder material and carbon. In some embodiments, the electrode film may further comprise one or more additives, such as a conductivity enhancing additive. In some embodiments, the electrode film of the cathode of a lithium ion capacitor may include one or more carbon-based electroactive components, such as, for example, a porous carbon material. In some embodiments, the cathode porous carbon material includes activated carbon. For example, the cathode electrode film can include a binder material, activated carbon, and a conductivity promoting additive. In some embodiments, the anode electrode film of a lithium ion capacitor includes an electrode film mixture that includes carbon configured to reversibly intercalate lithium ions. In some embodiments, the lithium intercalating carbon is graphite. For example, the anode electrode film can include a binder material, graphite, and a conductivity promoting additive.

[0031] In some embodiments, the binder material comprises one or more fibrillizable binder components. For example, the process of forming the electrode film can fibrillate the fibrillizable binder component such that the electrode film comprises a fibrillated binder. In some embodiments, the fibrillated binder comprises the superfibrillated binder particles described herein. The binder component may be fibrillated to provide a plurality of fibrils that are capable of binding one or more other components of the film. For example, a matrix, lattice and / or web of fibrils can be formed to provide a desired mechanical structure to the electrode film. For example, the cathode and / or anode of a lithium ion capacitor may be formed of one or more fibrils. One or more electrode films may be provided that contain a brilly binder component. In some embodiments, the binder component may include polytetrafluoroethylene (PTFE), ultra-high molecular weight polyethylene (UHMWPE), and / or other suitable fibrillizable materials, alone or in combination.

[0032] In some embodiments, the electrode film has a lower weight of binder material than previously known dry electrode films while maintaining desirable mechanical properties. In some embodiments, the electrode film has a lower weight of binder material than previously known dry electrode films while maintaining desirable mechanical properties. %, about 3 wt % to about 8 wt %, about 3 wt % to about 7 wt %, about 3 wt % to about 6 wt %, or about 3 wt % to about 5 wt % of binder material. In still other embodiments, the electrode film is an anode containing about 4 wt % to about 7 wt %, for example about 5 wt % to about 6 wt %, or about 6.5 wt % to about 8 wt %, of binder material. In some embodiments, the electrode film is a cathode containing about 7 wt % to about 11 wt %, for example about 8 wt % to about 10 wt %, of binder material with activated carbon. In some embodiments, the electrode film, such as the anode film, contains less than about 4 wt % or less than 3 wt %, for example about 0.5 wt % of binder material. % to 4% by weight, 1% to 4% by weight, 0.5% to 3% by weight, or 1% to 3% by weight. In some embodiments, electrode films with reduced amounts of binder can maintain desired resistance to tensile, shear, compressive and / or torsional stresses.

[0033] In some embodiments, the electrode film may have a lower amount of binder material compared to other materials in the film, allowing for a higher amount of conductivity-promoting additives to improve electrical performance. For example, anodes according to such embodiments may exhibit improved equivalent series resistance while maintaining or improving desired mechanical properties. In some embodiments, certain types of conductivity-promoting additives may be included in the electrode film to obtain desired electrical performance. For example, electrode films with lower binder material content may exhibit improved equivalent series resistance while exhibiting desired resistance to tensile, shear, compressive and / or torsional stresses, facilitating the manufacture of energy storage devices, such as lithium ion capacitors, with higher power density compared to other conventional energy storage devices of comparable construction.

[0034] In some embodiments, the conductivity-promoting additive comprises conductive carbon. In some embodiments, the conductive carbon comprises one or more of carbon black and / or graphite. In some embodiments, the one or more carbon blacks include commercially available {Shoyo}Ketjenblack® from Akzo Nobel NV, C-NERGY™ Super C65 from Imerys Graphite & Carbon, Ltd., Super P® from Imerys Graphite & Carbon, Ltd., BP2000® from Cabot Corp., and / or LITX® 50 from Cabot Corp. In some embodiments, the one or more graphites include commercially available ABG1010 from Superior Graphite Co. and / or ABG1005 from Superior Graphite Co. For example, the anode electrode film of a lithium ion capacitor can contain one or more conductivity-promoting additives described herein. In some embodiments, the conductive carbon is about 1% by weight in the electrode film mixture. In some embodiments, the conductive carbon content of the electrode film as described herein can be about 5% to about 10% by weight, including about 8% to about 8% by weight, or about 1% to about 5% by weight. % ESR improvement. In yet another embodiment, the conductive carbon has a surface area of ​​10 ~100m 2 / g, e.g. 20~50m 2 / g, and / or particle size of 0.1 to 10 μm. In yet another embodiment, the conductive carbon is characterized by a particle size of about 0.1 μm to about 0.5 μm, or about 10 μm. A lithium ion capacitor including an anode produced by the method has an ESR value of about 0.1 (m ohm) (milliohms) to about 10 (m ohm), for example, about 0.5 (m ohm) to about 5 (m ohm), or about 1.5 (m ohm) to about 3.5 (m ohm).

[0035] In some embodiments, one or more of the electrode films described herein are prepared using a dry process. The electrode film may be produced by a manufacturing process. As used herein, a dry manufacturing process may refer to a process in which no or substantially no solvent is used in forming the electrode film. For example, the components of the electrode film may include dry particles. The dry particles for forming the electrode film may be mixed together to obtain a dry particle electrode film mixture. In some embodiments, the electrode film may be formed from the dry particle electrode film mixture by a dry manufacturing process such that the weight percentages of the components of the electrode film and the weight percentages of the components of the dry particle electrode film mixture are comparable. In some embodiments, the electrode film formed from the dry particle electrode film mixture by a dry manufacturing process may be free or substantially free of any processing solvents and solvent residues resulting therefrom. In some embodiments, the electrode film formed from the dry particle electrode film mixture by a dry manufacturing process may be cleaner and / or structurally stronger, thereby resulting in improved electrochemical and / or mechanical performance. In some embodiments, the electrode film is a free-standing dry particle electrode film formed from the dry particle mixture by a dry process. In some embodiments, the free-standing dry electrode film consists essentially of or consists of dry carbon particles and dry ultrafibrillated binder particles. In some embodiments, only a single binder is used to form a free-standing dry electrode film, such as a single fibrillizable binder such as PTFE.

[0036] In some embodiments, the energy storage device is not a battery.

[0037] FIG. 2 illustrates an example process 200 for manufacturing an electrode film, according to some embodiments. FIG. 2 is a flow diagram illustrating a process 200 for manufacturing an electrode film. This is a dry process and does not use liquids or solvents such that the resulting electrode film is free or substantially free of liquids, solvents and residues. An electrode film mixture is formed that includes the particles and a binder material. Optionally, one or more The above conductivity enhancing additives can be mixed together. In some embodiments, the electrode film mixture is a dry particulate mixture. In some embodiments, the binder material is one or more of polytetrafluoroethylene (PTFE) and ultra-high molecular weight polyethylene (UHMWPE), etc. In some embodiments, the binder material consists or consists essentially of one polymer, such as PTFE. The conductivity enhancing additive can be one or more conductive carbons. For example, conductive carbons The composition may include one or more carbon blacks and / or graphites as described herein. This can be done.

[0038] In block 204, the binder in the electrode film mixture is ultrafibrillated to form ultrafibrillated The process of superfibrillation can form a fibrillated matrix. The process of superfibrillation can be performed by performing a conventional fibrillation process at a slower process speed and / or a higher process pressure. For example, the process of superfibrillation can be performed at a slower process speed and / or a lower pressure compared to that described in US Patent Application Publication No. 2015 / 0072234. In some embodiments, the process of superfibrillation can be a mechanical shear process. For example, a mechanical shear force can be applied to the binder material such that the binder material can be mechanically treated to form a plurality of fibrils therefrom. In some embodiments, the process of mechanical shear includes a mixing and / or milling process. For example, the rate at which the particles of the electrode film mixture are provided to and circulated through the blender and / or mill can be reduced during the process of superfibrillation. By slowing down the rate at which the particles of the electrode film mixture circulate through the blender and / or mill, the time that the particles of the electrode film mixture are circulated once through the process chamber of the blender and / or mill can be increased. In some embodiments, the circulation time can be increased to enhance fibrillation of the binder material, resulting in superfibrillation of the mixture. In some embodiments, the speed at which the particles of the electrode film mixture are circulated in the blender and / or mill can be determined so that the particles are circulated through the process chamber for about 1.2 to about 3 times longer than in conventional dry electrode processing. For example, the mixing and / or grinding process time in conventional dry processing can be about 1 minute. In some embodiments, the mixing and / or grinding time is about 2 minutes, about 3 minutes, about 4 minutes, about 5 minutes, about 7 minutes, or about 10 minutes. The mixing and / or grinding feed rate is: Compared to conventional dry electrode processing, the speed can be, for example, about half. In some embodiments, the feed rate of the mixing and / or grinding is about 10% of the rated machine feed rate, about 20% of the rated machine feed rate, about 30% of the rated machine feed rate, about 40% of the rated machine feed rate, about 50% of the rated machine feed rate, about 60% of the rated machine feed rate, about 70% of the rated machine feed rate, about 80% of the rated machine feed rate, or about 90% of the rated machine feed rate. In some embodiments, the electrode film is prepared by a process including a step of mixing and / or grinding a dry mixture of carbon particles and a binder for about 2 minutes to about 5 minutes.

[0039] In some embodiments, a continuous mixing process can be performed. In such embodiments, the mixing and / or grinding time can be inversely proportional to the feed rate. Thus, in such embodiments, the feed rate can be reduced compared to a conventional dry fibrillation process to increase the mixing and / or grinding time. In some embodiments, reducing this feed rate by half can double the mixing and / or grinding time. For example, the feed rate for conventional dry processing in a particular machine is about 50-60 kg / hr. Thus, in some embodiments, the ultrafibrillated binders or matrices provided herein can be produced on the same machine at feed rates of about 25-30 kg / hr. Generally, this feed rate will depend on the milling machine and can be adjusted based on the operating parameters of the machine in view of the disclosure herein. In yet other embodiments, larger channel equipment can be used to facilitate mixing and / or milling. In the case of batch mixing and / or grinding processes, the processing time can be increased simply by mixing and / or grinding for a longer period of time.

[0040] In some embodiments, the process pressure in the blender and / or mill during the fibrillation process can be increased to effect ultrafibrillation. In some embodiments, the increased process pressure increases the shear force applied to the binder material, thereby increasing the degree of fibrillation of the binder material. In some embodiments, the process pressure for ultrafibrillation can be determined such that the shear force applied to the binder material is about 1.2 to about 3 times the shear force in a conventional dry electrode fibrillation process.

[0041] The superfibrillation process, performed at slower processing speeds and / or higher processing pressures, may promote enhanced fibrillation of the binder material, promoting an increased number of fibrils formed from the binder material, increased fibril surface area, and / or longer fibril lengths. In some embodiments, slower processing speeds and / or higher processing pressures may enhance fibrillation to form an electrode film from a reduced amount of binder material that has a desired resistance to tensile, shear, compressive, and / or torsional stresses. For example, slower processing speeds and / or higher processing pressures may be used to reduce the amount of binder material while providing a desired resistance to one or more other components of the film. In some embodiments, the mixing step of block 202 and the fibrillation step of block 204 can promote the formation of a sufficient amount of fibrils to provide mechanical support for the fiber. The process may be one or substantially one continuous process.

[0042] In certain embodiments, the superfibrillation of block 204 is the same as a conventional fibrillation process. This can be done by repeating the process two or more times for the same material. The first fibrillation step can form a fibrillated matrix. This fibrillated matrix can then be reduced in size, e.g. A powdered electrode film mixture may be formed. For example, block 204 may include breaking down the first fibrillated electrode film mixture. Breaking the electrode film may include passing the fibrillated electrode film mixture through a strainer, sifter, mesh, riddle, screen, and / or sieve. The broken down fibrillated electrode film mixture may then be processed into a second fibrillated electrode film mixture as described herein. This second fibrillation step may be referred to herein as a superfibrillation step. As shown, the fibrillation step may be performed at a slower processing speed and / or a higher processing pressure. The second fibrillation step may result in a second powdered electrode film mixture. The second powdered electrode film mixture may then undergo further repetitions of the steps of block 204 or may undergo the steps of block 206. In this embodiment, a second (or additional) fibrillation step is performed to obtain an electrode filtrate with enhanced fibrillation. Thus, the superfibrillation of the binder in block 204 may be performed one, two, three or more times by fibrillation. Finally, in block 204, the ultrafibrillation process shown herein can be carried out after the sub-steps. A fibrillated matrix and / or ultrafibrillated binder particles are obtained.

[0043] At block 206, the fibrillated electrode film mixture is calendered in a calendering apparatus. Calendering machines are well known in the art and generally include a pair of calender rolls onto which raw materials, such as an electrode film mixture, are fed to form an electrode film. In some embodiments, the electrode film is formed in a first calendering step without additional calendering steps to form a film with a desired minimum thickness, as further described herein. In some embodiments, the calendered mixture can be a liquid, a solvent, , and forms a free-standing dry particulate film free or substantially free of residues resulting therefrom. In some embodiments, the electrode film is an anodic electrode film. In some embodiments, the electrode film is a cathodic electrode film. In some embodiments, the ultrafibrillated electrode film mixture can be calendered under selected conditions. For example, in still other embodiments, calendering can be performed at a temperature between 10 and 300° C. and a pressure between 5 and 150 kilonewtons. Calendering can be performed at a temperature between 10 and 300° C. and a pressure between 5 and 150 kilonewtons. They may be of any size selected for the application, but generally range in diameter from 5 to 80 cm. This is also fine. EXAMPLES

[0044] FIG. 3 is a table showing the equivalent series resistance of each of the lithium ion capacitor cells with anodes containing different types of conductivity promoting additives. The table shows the type of conductivity promoting additive contained in each capacitor anode and the corresponding equivalent series resistance in terms of a percentage improvement over a lithium ion capacitor without the conductivity promoting additive. The conductivity promoting additives tested included mesoporous carbon and various types of conductive carbon. As shown in FIG. 3, the lithium ion capacitors with anodes containing certain types of conductive carbons showed improved equivalent series resistance performance, while the lithium ion capacitors with anodes containing mesoporous carbons did not show a noticeable improvement in equivalent series resistance. For example, the lithium ion capacitors with anodes containing certain types of conductive carbons showed an equivalent series resistance improvement of 5% or more. showed improvement.

[0045] Also, lithium ion capacitors with anodes containing metal powders such as silver (Ag) powder, nickel (Ni) powder, or copper (Cu) powder did not show significant improvement in equivalent series resistance.

[0046] FIG. 4 illustrates a process 400 for manufacturing a thin electrode film, according to some embodiments. FIG. 4 is a flow diagram illustrating an example of a process for producing an electrode film. In some embodiments, the electrode film can be a cathodic electrode film. In some embodiments, the electrode film can be an anodic electrode film. In some embodiments, the process 400 for producing an electrode film is a dry processing process, which does not use liquids or solvents, and the resulting electrode film is In some embodiments, the process 400 is performed to generate a charge for an ultracapacitor, a battery, and / or a lithium An electrode of an ionic capacitor can be formed.

[0047] At block 402, ingredients of an electrode film mixture including a binder material and one or more conductivity enhancing additives can be mixed together. In some embodiments, the electrode film mixture is a dry particulate mixture. The binder material can be one or more fibrillizable polymers such as polytetrafluoroethylene (PTFE) and ultra-high molecular weight polyethylene (UHMWPE). In some embodiments, the binder material may include one type of binder, such as PTFE. In some embodiments, the conductivity-promoting additive comprises a polymer. For example, the conductive carbon may be one or more of the conductive carbons described herein. It may contain one or more types of carbon black and / or graphite.

[0048] At block 404, the electrode film mixture is mixed with the binder material to form fibrils. The composite can be fibrillated. The fibrillation process can be carried out at a slow processing speed and / or a high processing pressure. The slow processing speed and / or high processing pressure can promote enhanced fibrillation such that a reduced amount of binder material can be used to form an electrode film having a desired resistance to tensile, shear, compressive and / or torsional stresses. As described herein, in some embodiments, In some embodiments, the fibrillation process may include mechanical shearing, such as mixing and / or grinding. In some embodiments, the rate at which the particles of the electrode film mixture circulate through the blender and / or mill may be slowed down during the fibrillation process. In some embodiments, the process pressure inside the blender and / or mill during the fibrillation process may be increased. In some embodiments, the mixing and grinding steps of block 402 may be performed. and the fibrillation step of block 404 may be one or substantially one continuous step. Slower processing speeds and / or higher processing pressures can be used to produce electrode films having the above-mentioned greater strength, e.g., less than 120 μm or thinner than previously possible as described herein, via a single high pressure calendering step (single step), or multiple calendering steps (e.g., after an initial calendering step, the film is unwound and re-calendered one or more times).

[0049] In certain embodiments, block 404 can include reducing the size of the fibrillated electrode film mixture, e.g., by fracturing it, and refibrillating it, as described with reference to block 204 of FIG. Calendaring the fibrillated electrode film mixture to form a first electrode film. In block 408, the first electrode film can be unwound. For example, the first electrode film can be passed through a dispenser such as that shown in FIGS. 5A and 5B, which are described below. At block 410, the unwound electrode film can be re-calendered at least once. In some embodiments, the electrode film can have a thickness of about 50 μm or less. The thin electrode film may be recalendered two or more times to form a thin electrode film, such as a thickness of 100 mm or 150 mm or other thicknesses described herein. In some embodiments, the thin electrode film may be recalendered two or more times to form a thin electrode film, such as a thickness of 100 mm or 150 mm or other thicknesses described herein. The film is a free-standing dry particle electrode film that can exhibit the desired resistance to tensile, shear, compressive and / or torsional stresses. For example, the film can be calendered once. The thickness of the electrode film, such as a lithium ion capacitor anode electrode film, that has been passed through may be about 120 μm. The resulting electrode films with enhanced fibrillation described herein have high strength, and the calendered electrode film can be unwound and passed through the calender line one or more additional times to reach a thickness of less than about 120 μm. For example, the film may be calendered a second time to a thickness of, for example, about 80 μm or less. The recalendered anode electrode film is unwound and passed through the calender line a third time to produce an electrode film with a thickness of about 50 μm. can.

[0050] In some embodiments, the electrode film is less than 80 μm thick, or a conventional electrode film. Other electrode films described herein that are thinner than the cellulose acylate films are produced by passing the electrode film mixture with the ultrafibrillated binder through a calender line only once. For example, the calendering can be performed with sufficient pressure on the electrode film mixture such that a thickness of less than 80 μm can be achieved by calendering the mixture only once due to the high strength of the film resulting from its enhanced fibrillation. Reducing the electrode film to a desired thinness by running the electrode film mixture through a calendering apparatus only once can provide a cheaper and / or faster manufacturing process step.

[0051] Figure 5A is a schematic diagram of one embodiment of an unwinder for an electrode film calendering line. Figure 5B is a more detailed view of a portion of the unwinder shown in Figure 5A. The apparatus shown in Figures 5A and 5B can be used to perform the recalendering step 410 of Figure 4. For example, in the illustrated embodiment, a free-standing dry electrode film (shown as "unwound material" in FIG. 5B) is unwound and then recalendered with the pair of rollers shown. A calendering device similar to the rollers shown in FIGS. 5A and 5B can also receive and compress the dry electrode mix and form a second electrode film such as step 206 of FIG. 2 and step 410 of FIG. 4 or other embodiments. The first calendering step allows the initial formation of a free-standing dry electrode film. It will be understood that this is possible.

[0052] Figures 6A and 6B show SEM images of the dry electrode film matrix. SEM images of the dry electrode film matrix produced by conventional dry electrode processing are shown. FIG. 6B shows a graph of the nanofibrillation process prepared according to step 200 or other ultrafibrillation processes described herein. The dry electrode film matrix shown in FIG. 6A shows the electrode film with 8% binder. 6A and has a thickness of 80 μm. The electrode film of FIG. 6B contains 6.5% binder and has a thickness of 50 μm. The electrode film of FIG. 6B was produced from an electrode film mixture that was subjected to two grinding processes. As can be seen from a comparison of FIG. 6A and FIG. 6B, the dried electrode film matrix of FIG. 6B is characterized by enhanced binder fibrillation. Specifically, in FIG. 6B, the number of fibrils is increased. In FIG. 6A, a substantial portion of the carbon particles (shown in the figure) has a free surface, while in FIG. 6B, the fibrillated binder covers a substantially increased surface area of ​​the carbon particles. In general, the binder shown in FIG. 6B has a larger surface area and contacts the carbon particles with a larger surface area than the binder of FIG. 6A for the same mass. The binder of FIG. 6B is an example of a superfibrillated binder provided herein.

[0053] FIG. 7 shows the binder content, film thickness, capacitance, and ESR for lithium ion capacitors according to various embodiments comprising anodes made by the methods provided herein.

[0054] Although the present invention has been disclosed in the context of certain embodiments and examples, those skilled in the art will appreciate that the present invention extends beyond the specifically disclosed embodiments to other embodiments and / or other uses and modifications of the invention. In addition, while several variations of the embodiments of the present invention have been shown and described in detail, other modifications that are within the scope of the present invention will be readily apparent to those skilled in the art based on this disclosure. It is to be understood that various combinations or subcombinations of the specific features and aspects of these embodiments may be made and are within the scope of the present invention. It is to be understood that various features and aspects of the disclosed embodiments may be combined with or substituted for one another to form various other aspects of the disclosed embodiments of the invention. Thus, the scope of the invention disclosed herein should not be limited by the specific embodiments described above.

[0055] The headings used herein are for convenience only and do not necessarily affect the scope or meaning of the devices and methods disclosed herein.

Claims

1. A method for producing a dry electrode film for an energy storage device, comprising: forming a first dry electrode film mixture containing dry carbon particles and dry fibrillizable binder particles; superfibrillating the dry fibrillizable binder particles in the dry electrode film mixture at a feed rate of less than 50 kg / hr to form a superfibrillated matrix within the dry electrode film mixture, the superfibrillated matrix comprising dry superfibrillated binder particles; and calendering the ultrafibrillated dry electrode film mixture to form a free-standing ultrafibrillated electrode film. A method for producing a dry electrode film for an energy storage device.

2. The ultrafibrillating of the dried fibrillizable binder particles is carried out at a feed rate of 25 to 30 kg / hr. The method of claim 1 .

3. and ultrafibrillating the dried fibrillizable binder particles for at least 2 minutes. The method of claim 1 .

4. ultrafibrillating the dried fibrillizable binder particles is carried out for 2 minutes to 5 minutes. The method according to claim 3.

5. It is a dry process that uses substantially no processing additives; The method of claim 1 .

6. contacting the free-standing ultrafibrillated electrode film with a current collector to form a first electrode. The method of claim 1 .

7. forming a second electrode; and inserting a separator between the first electrode and the second electrode. The method according to claim 6.

8. The first electrode is an anode. The method of claim 7.

9. said calendering comprising compressing said free-standing superfibrillated electrode film to a thickness of 50 μm to 120 μm; The method of claim 1 .

10. The calendering to a thickness of 50 μm to 120 μm comprises a single calendering step; The method of claim 9.

11. the dried superfibrillated binder particles comprise 5% to 7% by weight of the superfibrillated matrix; The method of claim 1 .

12. forming the first dry electrode film mixture further comprises adding conductive carbon particles to the first mixture; The method of claim 1 .

13. The conductive carbon particles comprise a material selected from the group consisting of carbon black, conductive graphite, and combinations thereof. The method of claim 12.

14. The dried carbon particles include a porous carbon material. The method of claim 1 .

15. The porous carbon material is selected from the group consisting of activated carbon, porous graphite, and combinations thereof. The method of claim 14.

16. The dry ultrafibrillated binder particles are selected from the group consisting of polytetrafluoroethylene (PTFE), ultra-high molecular weight polyethylene (UHMWPE), and combinations thereof. The method of claim 1 .

17. the electrode film comprises 1% to 10% by weight of the dry ultrafibrillated binder particles; The method of claim 1 .

18. the superfibrillated matrix comprises carbon particles having at least 10% of their surface area in contact with the dry superfibrillated binder particles; The method of claim 1 .

19. The maximum dimension of the ultrafibrillated binder particles is up to 3 μm; The method of claim 1 .

20. The maximum dimension of the ultrafibrillated binder particles is a maximum of 0.01 μm to 3 μm; The method of claim 19.

Citation Information

Patent Citations

  • Dry particle-based electrochemical device and method for manufacturing the same

    JP2007531245A

  • Method of manufacturing electrode composite for secondary battery, electrode for secondary battery and secondary battery

    JP2011258333A

  • Electrode for electrochemical element

    JP2013077558A

  • Nonaqueous electrolyte secondary battery

    JP2015146249A